Этимология библейских имен собственных во французском языке - Шибаева, И.В. (Культура народов Причерноморья, 2003)
The work is dedicated to the problems of etymology of the Bible proper names in the French language. The etymology of male and female antroponyms and toponyms is given: hydronyms, oikonyms and oronyms. Three criteria are used: phonetic, morphologic and semantic. The brief summary of these correlations is made in order to orientate in etymological material.